EPIDEMIOLOGICAL FEATURES AND EVOLUTION OF CLINICAL PRESENTATION OF TYPHOID FEVER IN SAINT-PETERSBURG - K. E. Novak; A. G. Dyachkov; E. V. Esaulenko (Журнал инфектологии, 2019)
Purpose: To study an epidemiological features and evolution of clinical presentation of typhoid fever in modern megapolis Materials and methods: A study of 115 patient’s medical records was performed. All patients were hospitalized in Clinical Infectious Diseases Hospital named after S.P. Botkin, Saint-Petersburg, Russia during 2005–2017 with confirmed diag№sis of typhoid fever. We have conducted a comparison of epidemiological and clinical features between 59 patients hospitalized in 2005–2009 and 56 hospitalized in 2010–2017. Results: There was increase proportion of Central Asia’ countries citizens among study group during recent years. Social status of affected patients had also changed recently due to decrease fraction of homeless people along with decreased number of patients with accompanied infectious diseases. Atypical clinical presentation had become more common №wadays with most of a patients presented with moderate severity form of disease. Conclusion: Clinical presentation and epidemiology of typhoid fever are prone to changes over time. New data on epidemiology and predominance of atypical form of disease need to be considered to ensure prompt diag№sis of a disease.